Analisis Faktor-Faktor yang Memengharuhi NPF Pembiayaan UMKM di Perbankan Syariah Periode 2019-2022 - Muntashir, Abdul Hakim; Cupian, Cupian (Universitas Batanghari Jambi, 2024)
MSMEs are currently still the largest sector that supports the majority of Indonesian people, but MSMEs business development tends to be difficult considering that banking sector tends to be careful when providing financing to MSMEs because this sector has a high NPF ratio. Meanwhile, Bank Indonesia made regulations PBI Number 23/13/PBI/2021 that requiring banks to increase financing for MSMEs, this creates a dilemma for Islamic banking because this can make worsen the health of bank due to the higher NPF. This study examines the factors that could influence the NPF of MSMEs Islamic banking such as equivalent rate of working capital financing, equivalent rate of investment financing, ROA, the amount of financing, and Inflation. This research is a quantitative study using multiple linear regression to determine the direction and how much influence the independent variables have on the dependent variable. From this study it was found that the two types of equivalent rates have the opposite impact on NPF where Islamic banking can actually reduce the equivalent rates to help MSMEs development while reducing the NPF ratio because Islamic banking ROA is still in the very healthy category and ROA is directly proportional to NPF if it is increased. Then, if Islamic banking increases the amount of financing for MSMEs will reduce the NPF and the effect of inflation will not affect the increase in the NPF of MSMEs financing.